Urgensi Suatu Regulasi yang Komprehensif Tentang Fintech Berbasis Pinjaman Online Sebagai Upaya Perlindungan Konsumen di Indonesia - Disemadi, Hari Sutra; Regent, Regent (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The existence of human civilization has entered a comprehensive stage of progress, the real form of this progress can be seen from the increasingly advanced development of information and communication technology. These technological advances have also been exploited in the financial transaction sector with the presence of technology-based financial institutions (fintech). The formation of laws that specifically regulate the implementation of the fintech industry, especially online fintech loans, is very necessary because the current regulations have not been able to fully accommodate legal issues that arise in the implementation of online lending fintech activities. One of the most crucial problems that arise in the implementation of fintech activities is the absence of strict sanctions that can be used by law enforcers in eradicating illegal online loan fintech service providers whose existence often violates the rights of public consumers. With the enactment of a law that specifically regulates the implementation of online loan fintech services, it is hoped that it can provide guarantees and legal certainty, especially in protecting people's rights.